Determination of The Status of Utilization and Level of Sepat (Trichogaster sp) in Public Waters of Mainland Banjar Regency - Irhamsyah Irhamsyah; Novita Sari; Iriansyah Iriansyah (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2019)
The fishing of Sepat (Trichogaster sp) in freshwaters of Banjar Regency with a solid intensity that has lasted long enough. This study aims: (1) Knowing the model of surplus production that can be used. (2) Knowing the optimum effort Sepat (3) Knowing maximum sustainable yield. (4) Knowing the utilization level of Sepat. (5) Knowing the effort level of Sepat. The method that used in this research is survey method and collecting data. Data is analyzed by the Schaefer’s model and Fox’s model. The result of this research: (1) The best model is the Schaefer model with R2 and validation value. (2) The catch rate of Sepat is 45630 trip per year. (3) Maximum sustainable yield of Sepat is 45,466 ton per year. (4) The utilization rate of Sepat (Trichogaster sp) is 33% which shows there has been no more catch under fishing (5) Effort level of Sepat is 16 %.